Kontribusi Managerial Perpustakaan, Motivasi Orang Tua Dan Fasilitas Perpustakaan Terhadap Minat Membaca Siswa Sma Negeri 1 Pulokulon Grobogan - Rahayu, Puji; , Prof. Dr. Sutama, M.Pd (2017)
This research uses quantitative methods, this study was conducted in SMA N 1 Pulokulon Grobogan. The results of the study, (1) There is a positive contribution managerial library, the motivation of parents and library facilities to the reading interests of students at SMA Negeri 1 Pulokulon (F =136.464 and p <0.05), so the hypothesis is accepted. Effective contribution of independent variables managerial library, the motivation of parents and library facilities to the reading interests of students at SMA Negeri 1 Pulokulon simultaneous amounted to 72.3% and the remaining 27.7% is influenced by other variables not included in this study. (2) There is a positive contribution to the library between managerial interest in reading students in SMA Negeri 1 Pulokulon (t = 4.442 and p <0.05), which means the higher managerial then the library will be higher the students' interest in reading, conversely the lower the managerial library it will also lower the students' interest in reading, so that the second hypothesis in this study received. Large library of managerial effective contribution to the reading interests of students at SMA Negeri 1 Pulokulon by 20.52% while the relative contribution of 28.31%. (3) There is a positive contribution to the motivation of parents for students' reading interest in SMA Negeri 1 Pulokulon (t = 5.025 and p <0.05), which means the higher the motivation of the parents, the higher the students 'interest in reading, conversely the lower the motivation of the parents then the lower the students' interest in reading, so that the third hypothesis in this study received. Large effective contribution motivation of parents for students' reading interest in SMA Negeri 1 Pulokulon 18.99% while the relative contribution of 26.26%. (4) There is a positive contribution to the library includes reading interests of students at SMA Negeri 1 Pulokulon (t = 6.561 and p <0.05), which means the higher the library facilities, the higher the students' interest in reading, conversely the lower the amenities library it will also lower the students' interest in reading, so that the fourth hypothesis in this study received. Effective contribution of library facilities to students' reading interest in SMA Negeri 1 Pulokulon 33.43% while the relative contribution of 46.23%. Keywords: motivation, parents, libraries